THE AMERICAN UNIVERSITY OF NIGERIA’S INTERVENTIONS IN MITIGATING THE BOKO HARAM INSURGENCY IN NORTHEAST NIGERIA: A CASE STUDY OF A DEVELOPMENT UNIVERSITY (AUN INTERNATIONAL CONFERENCE, 2024)
The Boko Haram insurgency in Northeast Nigeria has precipitated a complex humanitarian crisis characterized by mass displacement, loss of lives, and socioeconomic disruption. Different development assistance organizations, such as the United States Agency for International Development (USAID), Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ), United Nations Development Program (UNDP), and United Nations Population Fund (UNFPA), have intervened to mitigate the adverse effects of Boko Haram terrorism in the northeast and Nigeria generally. These organizations’ activities have received scholars’ attention; however, the American University of Nigeria (AUN), a development university in the heart of the conflict zone, has received limited critical attention on its roles in combating the Boko Haram menace. This paper holistically examines AUN's strategic interventions in education, community engagement, and peacebuilding, underscoring the pivotal role of development universities in crisis mitigation and community resilience, especially in the developing world. Such initiatives include the Chibok Girls Education Initiative, the Feed and Read program, the Waste to Wealth project, and the AUN Adamawa Peace Initiative (API). Through these humanitarian-centered programs, AUN demonstrates its dedication to fostering human capital, empowering vulnerable populations, and promoting a culture of peace to alleviate Boko Haram terrorism. This research highlights the potential of development universities as agents of positive change in conflict-ridden societies, providing a model for community-engaged higher education institutions seeking to contribute to sustainable development and post-conflict recovery. By uniting research efforts and translating findings into action, AUN exemplifies the transformative power of knowledge and humanitarianism in combating security challenges and building a more resilient future for Northeast Nigeria.